The role of polymorphic variants of arginase genes (ARG1, ARG2) involved in beta-2-agonist metabolism in the development and course of asthma - O. N. Savelieva; A. S. Karunas; Yu. Yu. Fedorova; R. R. Murzina; A. N. Savelieva; R. F. Gatiyatullin; E. I. Etkina; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции, 2020)
Asthma is a common severe disease of the respiratory tract, it leads to a significant impairment in the quality of a patient’s life unless effectively treated. Uncontrolled asthma symptoms are a cause of disease progression and development, they lead to an increase in the patient’s disability. The sensitivity to asthma therapy largely depends on the interaction of genetic and epigenetic factors, which account for about 50–60 % of variability of therapeutic response. Beta-2-agonists are some of the major class of bronchodilators used for asthma management. According to published data, allelic variants of the arginase ARG1 and ARG2 genes are associated with a risk of asthma development, spirometry measures and efficacy of bronchodilator therapy. High arginase activity results in a low level of plasma L-arginine and in a decrease in nitric oxide, and, as a result, in an increase in airway inflammation and remodeling. Arginase genetic polymorphisms (rs2781667 of the ARG1 gene, rs17249437, rs3742879, rs7140310 of the ARG2 gene) were studied in 236 children with asthma and 194 unrelated healthy individuals of Russian, Tatar and Bashkir ethnicity from the Republic of Bashkortostan. Association analysis of the studied polymorphisms with asthma development and course, the sensitivity to therapy in patients was carried out. It was found that the rs2781667*C allele of the ARG1 gene is a marker of an increased risk of asthma in Tatars. In Russians, the association of rs17249437*TT and rs3742879*GG genotypes of the ARG2 gene with a decrease in spirometry measures (FEV1, MEF25) was established. In Russians and Tatars receiving glucocorticoid monotherapy or combination therapy, the association of the rs17249437*T allele and rs17249437*TT genotype of the ARG2 gene with a partially controlled and uncontrolled course of asthma was shown.